Bāṃlādeśera Saṃskr̥ti o Saṃskr̥tibidyā - Bāṃlādeśera Saṃskr̥ti o Saṃskr̥tibidyā (Seminar) (2014 : Rajshahi University, Institute of Bangladesh Studies); Kāmāla, Ema. Mostaphā; Rajshahi University. Institute of Bangladesh Studies (Rājaśāhī : Inasṭiṭiuṭa Aba Bāṃlādeśa Sṭāḍija, Rājaśāhī Biśvabidyālaẏa, 2017)
Articles on cultural history of Bangladesh; compilation of seminar papers.
Includes bibliographical references.
In Bengali; includes portion in English.
Keywords: Bangladesh -- Civilization -- Congresses; Folklore -- Bangladesh -- Congresses; Folklore -- Bangladesh -- Congrès.; Civilization; Folklore; Bangladesh; Conference papers and proceedings